Adrianto, H. (2020). Pembelajaran biologi sel dengan peraga sederhana. Jurnal Pengabdian Barelang, 2(1), 7–12. https://doi.org/10.33884/jpb.v2i01.1619 Afandi, Tulus, J., & Rachmi, A. (2016). Implementasi digital-age literacy dalam pendidikan abad 21 di Indonesia. Seminar Nasional Pendidikan Sains, 113–120. https://www.neliti.com/publications/173402/implementasi-digital-age-literacy-dalam-pendidikan-abad-21-di-indonesia Alfi, C., Sumarmi, & Amiruddin. (2016). Pengaruh pembelajaran geografi berbas - Wardani, Asri Ainun; Syamsudduha, St.; Syamsul, Syamsul (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aimed to examine the effect of Couple Card learning media on the learning outcomes of eleventh-grade students at SMAN 13 Makassar in the topic of the human movement system. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The study population consisted of 136 eleventh-grade students. The sample was selected through multistage random sampling, resulting in Class XI MIA 1 being assigned as the experimental group and Class XI MIA 2 as the control group. Each group comprised 15 students. Learning outcome data were collected using an achievement test and analyzed through descriptive and inferential statistical procedures. The inferential analysis included tests of normality, homogeneity of variance, and an independent-samples t-test. The results showed that the experimental group obtained a mean posttest score of 90.5, whereas the control group achieved a mean score of 84.4. The independent-samples t-test yielded a two-tailed significance value of 0.013, which was lower than the significance level of 0.05. These findings indicate a statistically significant difference in learning outcomes between the experimental and control groups. Therefore, the use of Couple Card learning media had a significant effect on students’ learning outcomes in the topic of the human movement system and may be considered a viable alternative instructional medium in biology education.